2018
DOI: 10.3892/ol.2018.7844
|View full text |Cite
|
Sign up to set email alerts
|

Blood supply characteristics of pedunculated hepatocellular carcinoma prior to and following transcatheter arterial chemoembolization treatment: An angiographic demonstration

Abstract: Abstract. Pedunculated hepatocellular carcinoma (P-HCC) is a rare type of HCC, defined as a carcinoma protruding from the liver with or without a pedicle with a low degree of liver invasion. The present study aimed to evaluate the characteristics of blood supply of P-HCC prior to and following transcatheter arterial chemoembolization (TACE) treatment. Angiographic findings prior to and following TACE treatment in 39 patients with P-HCC were analyzed retrospectively. Angiography performed at the first TACE sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…7 However, because tumor neovascularization can rapidly restore tumor blood supply after TACE, TACE alone is not generally considered a potentially curative treatment for HCC. 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, because tumor neovascularization can rapidly restore tumor blood supply after TACE, TACE alone is not generally considered a potentially curative treatment for HCC. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 However, because tumor neovascularization can rapidly restore tumor blood supply after TACE, TACE alone is not generally considered a potentially curative treatment for HCC. 8 An alternative minimally invasive approach to treating HCC involves the use of thermal ablation, and this has been shown to be potentially curative for small (⩽3 cm) HCC. 9 However, conventional energy ablation techniques for treating HCC have typically used only a single antenna to deliver energy, resulting in relatively small ablation zones and increased risks of local tumor residual, intrahepatic recurrences, or distant metastases, particularly in intermediate-sized (⩽5 cm) HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Huang Juan’s study of 50 cases of HCC, 36 (72%) were supplied by hepatic arterial blood, 6 (12%) by arterial combination with portal blood supplying, 4 (8%) by portal blood supply, and 4 (8%) with poor blood supplying. [ 26 ] Another earlier study also found that although most HCC lesions can be detected in the arterial phase, some can only be detected in the portal or delayed phase. [ 21 ] According to another study, [ 27 ] up to 79.5% of patients will have a new extrahepatic collateral supply after TACE.…”
Section: Discussionmentioning
confidence: 97%